The Effect Of Mindfulness Therapy On Fear Of Missing Out Among Adolescents Aged 17–18 Years - Hanim Nur Faizah; Karyo Karyo; Lukman Hakim; Tasbiqatul Fitriyah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
High-intensity social media use among adolescents can trigger anxiety and psychological stress, driving continuous information-seeking and social comparison, a phenomenon known as Fear of Missing Out (FoMO). This study aims to analyze the effect of mindfulness therapy on reducing FoMO levels and to contribute to developing mindfulness-based mental health interventions for adolescents.Employing a quantitative approach, this study utilized a pre-experimental, one-group pre-post-test design. A sample of 100 adolescents was selected via purposive sampling based on specific inclusion and exclusion criteria. Data were collected using a content- and construct-validated FoMO questionnaire.The analysis revealed a significance value of 0.000 (p < 0.05), indicating a significant effect of mindfulness therapy on reducing adolescent FoMO levels. Furthermore, an effect size of 0.95 demonstrated a large practical intervention effect. Consequently, mindfulness therapy is not only statistically effective but also holds substantial practical implications as a potential intervention to mitigate FoMO and enhance the psychological well-being of adolescents in the digital age.